Instagram dalam Perspektif Kapitalisme Lanjut - Wijaya, Roni; Putranto, Algooth (Magister of Communication Science, Sahid University Jakarta., 2023)
Instagram is one of the largest social media platforms in the world which has more user growth figures compared to Facebook. The reason is that Instagram prioritizes visuals and makes it easier to share photos and videos, has become the target of business accounts, there are more and more features, and there are many supporting applications that make it easier for Instagram users to organize their photos, it has been owned by Facebook since 2012 and is connected to Facebook. This study aims to study how the Instagram platform is from the perspective of advanced capitalism. The business of providing the Instagram social media platform can be seen as a practice of advanced capitalism. This is based on the reason that the Instagram social media platform is in line with the three pillars of capitalism, namely exploitation, expansion, accumulation, and the government's role in the business process.